Sexual abuse on Nigerian female children - Uche Megafu; Uche Okafor; Ifeoma Emodi (International Journal of Medicine and Health Development, 1998)
Fifty-six cases of sexual abuse on Nigerian female children have been analysed. Cases of sexual abuse represent 0.8% of all cases referred to the consultant gynaecological/Paediatric out-patient clinics. Cases of sexual abuse on Nigerian children may be much more than we have reported since most parents and guardians do not like to report such cases to doctors or the law enforcement agents. Various forms of sexual abuses have been defined.